THE EFFECT OF REPLACEMENT COMMERCIAL RATION WITH BREAD WASTE ON COMMERCIAL CARCASS PIECES OF KAMPUNG UNGGUL BALITNAK (KUB) CHICKENS - M. R., Damanik; Siti, N. W.; Sukmawati, N. M. S. (Jurnal Peternakan Tropika; Vol 10 No 2 (2022): Vol. 10 No. 2 Tahun 2022; May - August, 2022)
This study aimed to determine the effect of replacement commercial rations with bread waste on commercial carcass pieces of Kampung Unggul Balitnak (KUB) chickens. This research was carried out for 8 weeks in the cage owned by Mr. Gede Suarta which is located on Gulingan Village, Mengwi District, Badung Regency, Bali. The experimental design used was a completely randomized design (CRD) consisting of 3 treatments and 5 replications, so there were 15 experimental units. Each experimental unit contained 2 heads KUB chickens aged of one week with a body weight range of 44 ± 2 g. The treatments were: KUB chickens fed 100% commercial 511 ration without bread waste (P0), KUB chickens fed 75% commercial 511 ration + 25% bread waste (P1), and KUB chickens fed 50% commercial 511 ration + 50% waste bread (P2). The variables observed were carcass weight, carcass percentage, thigh percentage, drumsticks percentage, wings percentage, chest percentage, and back percentage. The results showed that KUB chickens fed 75% commercial rations + 25% of bread waste (P1) and 50% commercial rations + 50% of bread waste (P2) had a carcass weight significantly (P<0.05) lower than P0 treatment (100% commercial ration) of 16.05% and 23.16% respectively, but the percentage of carcass and commercial carcass pieces (thighs, drumsticks, chest, wings, and back) were equal among all treatments (P>0.05). The conclusion of this study is that the replacement of commercial rations with bread waste as much as 25% and 50% in KUB chickens can produce a percentage of carcasses and commercial pieces of carcass (upper thigh, lower thigh, chest, wings, and back) equal to 100% commercial rations, but in carcass weight decreases. Keywords: KUB chickens, carcass weight, commercial carcass pieces, bread waste